A cross sectional study of animal and human colonization with Methicillin-Resistant Staphylococcus aureus (MRSA) in an Aboriginal community. (December 2016) - Daley, Peter; Bajgai, Janak; Penney, Carla; Williams, Karen; Whitney, Hugh; Golding, George; Weese, Scott
Abstract Background Methicillin-resistantStaphylococcus aureus (MRSA) infections are common among humans in Aboriginal communities in Canada, for unknown reasons. Methods Cross sectional study of humans and dogs in an Aboriginal community of approximately 1200 persons. Our objectives were to measure community-based prevalence of nasal MRSA colonization among humans, use multivariable logistic regression to analyze risk factors for MRSA colonization, and perform molecular typing ofStaphylococci isolated to investigate interspecies transmission. Results 461 humans were approached for consent and 442 provided complete data. 109/442 (24.7 %, 95 % C.I. = 20.7–28.7 %) of humans were colonized with MRSA. 169/442 (38.2 %) of humans had received antibiotics in the last 12 months. Only number of rooms in the house (OR 0.86, p = 0.023) and recreational dog use (OR 7.7, p = 0.002) were significant risk factors for MRSA colonization. 95/109 (87.1 %) of MRSA strains from humans were of the same spa type (CMRSA10/USA300). 8/157 (5.1 %, 95 % C.I. = 1.7–8.5 %) of dogs were colonized with methicillin-susceptibleS. aureus, and no dogs were colonized with MRSA. Conclusions Human MRSA colonization in this community is very common, and a single clone is predominant, suggesting local transmission. Antibiotic use is also very common. Crowding may partially explain high colonization, but most considered risk factors including animal exposure were not predictive. Very few dogs carried human Staphylococcal strains.